ACCIDENT AT «FUKUSHIMA-»I NPP: FIRST RESULTS OF EMERGENCY RESPONSE REPORT 2: ACTIVITIES OF THE ROSPOTREBNADZOR AUTHORITIES FOR THE RADIATION PROTECTION OF THE RUSSIAN FEDERATION POPULATION ON THE EARLY STAGE OF ACCIDENT - G. G. Onischenko; I. K. Romanovich; A. N. Barkovsky; G. Ya. Bruk; V. Yu. Golikov; A. A. Gorsky; M. V. Kaduka; Yu. O. Konstantinov; A. S. Mishin; V. P. Ramzaev; V. S. Repin; V. N. Shutov; et al. (Радиационная гигиена)
Basic measures of the Rospotrebnadzor emergency response during the early stage of the «Fukushima-I» NPP radiation accident are being analyzed in the article. Radiation monitoring of the environmental objects of the territories of the Russian Federation Far East Federal District, radiation control of arriving from Japan vehicles, freights and passengers as well as imported from Japan food products were promptly organized. This allowed to get reliable evaluations of the levels of radioactive contamination at the Russian Federation territory and population exposure doses due to the «Fukushima-I» NPP accident, timely exclude the possibility of import to the Russian territory for the freights, vehicles, food products having contamination exceeding established in the Russian Federation standards.